The challenge of decarbonisation and EU-Turkey trade relations: A long-term perspective - Kadri Tastan (Stiftung Wissenschaft und Politik (SWP), 2022)
The implementation of the European Union's (EU) Green Deal to reduce emissions by 2030 and to achieve climate neutrality by 2050 will have an impact on the EU's trade policy and on its trade relations with its non-EU partners. With the ongoing decarbonisation process of European economic sectors, the EU's climate policy will be increasingly integrated into its trade policy through measures such as the Carbon Border Adjustment Mechanism (CBAM) and by strengthening the environment chapters of its trade agreements. Therefore, the debate on the future of Turkey-EU trade relations should focus on future prospects for decarbonisation and trade if both sides are keen to maintain or deepen their trade relations. In the current context, which is rife with geopolitical and energy security considerations, a long-term vision and a holistic approach are needed now more than ever.
Keywords: 320; Green Deal; Decarbonisation; Carbon Border Adjustment Mechanism; CBAM; Nationally Determined Contributions; NDCs; Customs Union; Transatlantic Trade and Investment Partnership; TTIP; EU Emissions Trading System; Turkey